Pengaruh Sistem Informasi Akuntansi, Pengendalian Internal, dan Budaya Organisasi Terhadap Kinerja Perusahaan - Fahmi, Izzudin; Suwandi, Suwandi (Universitas Muhammadiyah Gresik, 2024)
This study aims to examine and analyze the influence of accounting information systems, internal control, and organizational culture on company performance. The research also provides strategic recommendations to help companies improve their performance and achieve desired outcomes. The study employs a quantitative approach, with data collected through surveys. Closed-ended questionnaires using a likert scale were distributed to predetermined respondents. The findings reveal that accounting information systems and internal control do not significantly influence company performance, whereas organizational culture has a significant impact. Based on these findings, it is concluded that organizational culture plays a crucial role in enhancing company performance. The implication of this research is to offer guidance for companies to focus more on strengthening organizational culture as a primary strategy to achieve optimal goals and outcomes.